1998
DOI: 10.1063/1.869815
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of a lobed fuel injector

Abstract: Numerical modeling of the nonreactive mixing processes associated with a lobed fuel injector in a coflowing air stream is presented. The lobed fuel injector is a device which generates strong streamwise vorticity, producing locally high strain rates which can enhance the molecular mixing of reactants while delaying ignition in a controlled manner. Vortex element modeling is used to simulate flow field evolution and fuel element mixing characteristics for this lobed fuel injector. Quantitative predictions for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…The effect of this skewing on the ow evolution was determined by making a comparison of experimental observationssuch as those in Fig. 6 with numerical simulations of the lobed injector ow eld, using the vortex element method previously used and described in detail by Strickland et al 2 Details on the present simulation may be found in Ref. 26.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of this skewing on the ow evolution was determined by making a comparison of experimental observationssuch as those in Fig. 6 with numerical simulations of the lobed injector ow eld, using the vortex element method previously used and described in detail by Strickland et al 2 Details on the present simulation may be found in Ref. 26.…”
Section: Resultsmentioning
confidence: 99%
“…The lobed injector shapes, incorporating vertical or essentially vertical side walls, were designed on the basis of their potential for vorticity generation and rollup as predicted by an incompressible simulation of the ow eld. 2 Lobed mixers with vertical side walls are similarly observedto enhancestreamwise vorticity generation. 5¡9 All three injectors were fabricated of aluminum using an electrical discharge machining (EDM) device, and all three had the same injectant gap width (0.381 mm) and wall thickness (0.584 mm).…”
Section: Experimental Facility and Methodsmentioning
confidence: 99%
“…4a. Injector B2 was an alternative fuel injector design, based on the results of numerical simulations of the lobed injector flowfield, 13 which showed a propensity for this shape to generate stronger streamwise vorticity. The lobed injectors were all constructed of aluminum using electricdischarge machining.…”
Section: Experimental Facility and Methodsmentioning
confidence: 99%
“…In addition, several numerical studies have been performed to study the three-dimensional flow field downstream of the lobed mixer. Originally, a steady RANS approach in conjunction with a turbulence model (38)(39)(40)(41)(42) and a vortex-element approach (43) were used to calculate lobed mixer flows, and the effect of boundary conditions on the numerical results were also considered in these studies (39)(40)(41) . Subsequent studies with regard to mixing characteristics of lobes have simulated multiple or realistic lobed nozzles using a large-eddy simulation (LES) approach (44,45) .…”
Section: Introductionmentioning
confidence: 99%